Trends of robotic-assisted surgery for thyroid, colorectal, stomach and hepatopancreaticobiliary cancer: 10 year Korea trend investigation - Liang An; Kyo Sun Hwang; Shin-Hoo Park; You Na Kim; Se-Jin Baek; Sungsoo Park; Woo Jin Hyung; Woung Youn Chung; Seon-Hahn Kim (Asian Journal of Surgery, 2021)
Background: The current position of robotic surgery in the field of minimally invasive surgery remains ambiguous. We evaluated long-term trends of robotic general surgery and the future direction of its development. Methods: Data on robotic cancer surgeries between 2005 and 2014 were retrospectively collected by volunteer institutions in the Republic of Korea. Spearman's correlation and logistic regression analyses were used to compare robotic and laparoscopic surgery trends in general surgery. Results: The odds that robotic surgery was performed instead of laparoscopic surgery significantly decreased in the fields of colorectal, stomach, and hepato-biliary-pancreatic surgery (odds ratio [OR]: 0.95, 95% confidence interval [CI]: 0.93–0.97; OR: 0.90, 95% CI: 0.88–0.92; and OR: 0.71, 95% CI: 0.65–0.78, respectively), except for thyroid surgery (OR: 1.28, 95% CI: 1.25–1.30). Of the total numbers of each procedure, proportions of robotic intersphincteric resections, abdominoperineal resections, and pylorus-preserving surgery performed significantly increased (r = 0.98, P < .001; r = 0.78, P = .01; and r = 0.86, P = .007, respectively). Conclusions: The use of robotic surgery failed to preponderate that of laparoscopic surgery, except for thyroid surgery. Robotic surgery is increasingly preferred for limited fields or complex surgeries, but the use of robotics in simple surgeries has decreased.